1998
DOI: 10.1029/98jd00208
|View full text |Cite
|
Sign up to set email alerts
|

Non local thermodynamic equilibrium (LTE) atmospheric limb emission at 4.6 μm: 2. An analysis of the daytime wideband radiances as measured by UARS improved stratospheric and mesospheric sounder

Abstract: Abstract. An analysis of the measurements taken by the improved stratospheric and mesospheric sounder (ISAMS) in its carbon monoxide wideband channel around

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…SAMS and ISAMS measurements near 4.3 μm are less sensitive to these rates. López‐Puertas and Taylor [] and López‐Puertas et al [, ] analyzed those observations including values of 2·10 −11 and 2.4·10 −12 cm 3 s −1 . These values were based on the measurements of Jacobs et al [] of 2·10 −11 cm 3 s −1 for the redistribution between the 10001 and 10002 levels, and on the results of Finzi and Moore [] who found that the redistribution of the v 1 and v 2 quanta is independent of the vibrational excitation of the v 3 mode.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…SAMS and ISAMS measurements near 4.3 μm are less sensitive to these rates. López‐Puertas and Taylor [] and López‐Puertas et al [, ] analyzed those observations including values of 2·10 −11 and 2.4·10 −12 cm 3 s −1 . These values were based on the measurements of Jacobs et al [] of 2·10 −11 cm 3 s −1 for the redistribution between the 10001 and 10002 levels, and on the results of Finzi and Moore [] who found that the redistribution of the v 1 and v 2 quanta is independent of the vibrational excitation of the v 3 mode.…”
Section: Discussioncontrasting
confidence: 67%
“…The same rate was used by Funke et al []. Only the analysis of ISAMS measurements [ López‐Puertas et al , , ] suggested that a factor between 0.8 and 1.0 times the rate of Inoue and Tsuchiya [] was consistent with ISAMS radiances taken at a SZA lower and higher than 60°, respectively. In our analysis we use the fit k v v ,0 =4.64·10 −13 (300/ T ) 0.64 to the measurements of Inoue and Tsuchiya [], which is very similar to the usual form of kvv,0=5·1013300/T (see Figure a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are other uncertainties to consider in a retrieval under non-LTE conditions. Specifically, C0 2 is apparently not well mixed above 75 km [Lopez-Puertas et al, 1998b]. Uncertainties in CO2 will manifest themselves as uncertainties in the retrieved mesospheric temperature.…”
Section: Resultsmentioning
confidence: 99%